2004
DOI: 10.1002/chem.200400342
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Total Synthesis of the New Anticancer Agent Mensacarcin: Synthesis of the Carbocyclic Core

Abstract: A synthesis of the carbocyclic core associated with the new anticancer agent mensacarcin (1) is reported. The strategy involves the synthesis of several novel highly substituted aromatic compounds, such as 12 and 23. The lithium derivative of 12 readily engages in a nucleophilic addition to benzaldehyde 4 to provide the diphenylcarbinol rac-15. The analogous benzyl ether rac-16 undergoes an intramolecular Heck reaction to provide the required tetrahydroanthracene rac-17, which can be transformed into the key t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 42 publications
0
25
0
1
Order By: Relevance
“…For the synthesis of 11 1,5-dihydroxynaphthalene (12) was oxidized with air in the presence of CuCl in the dark to give juglone (13), which was subsequently methylated with methyl iodide in the presence of silver(i) oxide to afford Omethyljuglone (11; Scheme 3). [14] Scheme 3.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…For the synthesis of 11 1,5-dihydroxynaphthalene (12) was oxidized with air in the presence of CuCl in the dark to give juglone (13), which was subsequently methylated with methyl iodide in the presence of silver(i) oxide to afford Omethyljuglone (11; Scheme 3). [14] Scheme 3.…”
Section: Synthesismentioning
confidence: 99%
“…[10][11][12] Another approach, which has recently been developed by us, is based on two disconnections in ring B and employs an addition of a metal-organic species obtained from 3 to the aldehyde 4 to give 5. [13] The latter can easily be transformed into 6 by a Pd-catalyzed arylation (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Gç C4/4, found in a soil sample by the cafeteria (Mensa) at the University of Gçttingen) in 1998. [1] It has nine stereogenic centers including two epoxide groups (Scheme 1) and is closely related to cervicarcin (2), an antitumor antibiotic produced by Streptomyces ogaensis. [2][3][4] In an antitumor activity assay performed by Beil, [5] mensacarcin showed an average total growth inhibition (TGI) value of 1.3 mm against 60 cell lines, which is comparable to that of doxorubicin (3; TGI= 1.9 mm), one of the most widely used agents for antitumor therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Feeding of isotope-labeled materials: For the feeding of 13 C-labelled compounds, sodium [1][2][3][4][5][6][7][8][9][10][11][12][13] C]acetate (750 mg), sodium [1,2-13 C 2 ]acetate (450 mg), and l-[methyl-…”
mentioning
confidence: 99%
“…[39] Mensacarcin represents a rather unique compound containing nine stereogenic centers and two epoxide moieties. Beside our efforts towards the total synthesis of mensacarcin (1), [26,40,41] we were also interested in preparing simplified analogs and partial structures for further investigations of the structure-activity relationship. Basic studies of mensacarcin (1) have already shown that the epoxide-containing side chain acts as the main pharmacophore and that a reductive opening of the latter led to a dramatic decrease of the cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%